How different is pyrimidine as a core component of DNA base from its diazine isomers: A DFT study?. Issue 24 (22nd August 2016) - Chatterjee, Subhojyoti; Wang, Feng
Abstract: Recent photoemission spectroscopic (X‐ray photoemission spectra) study revealed less dramatic chemical changes for pyrimidine (PyM, 1, 3‐diazine) with in its ionization potential. Present systematic study using density functional theory calculations shows that PyM is indeed quite different from its diazine isomers (PyD, 1, 2‐diazine and PyA, 1, 4‐diazine). It is discovered that the most stable isomer PyM is relaxed from C2V to C1 point symmetry with a total electronic energy deduction of −15.86 kcal.mol −1 . Although not substantial, PyM has the smallest molecule shape (electronic spatial extent) and the largest HOMO‐LUMO energy gap of 5.65 eV; only one absorption band in the region of 200–300 nm of the UV‐Vis spectrum but three clusters of chemical shift in the carbon and hydrogen NMR spectra. The energy decomposition analyses revealed that the interaction energy (Δ E Int ) of PyM is preferred over PyA by 4.08 kcal.mol −1 and over PyD by 22.32 kcal.mol −1, with the preferred NCN bond revealed by graph theory. Abstract : The question of why nature chooses pyrimidine as a core component of DNA bases over other diazine isomers, that is, pyrazine and pyridazine, requires an investigation at the molecular level. In addition to being the most stable isomer, pyrimidine possesses unique properties including a single absorption band in the region of 200–300nm UV‐Vis spectrum and s‐like HOMO. Pyrimidine is also the preferred structure in the energy decomposition analyses with the favorite NCN bond revealed by graph theory.